Collaboration in the Digital Age : How Technology Enables Individuals, Teams and Businesses - Riemer, Kai; Schellhammer, Stefan; Meinert, Michaela (Progress in IS., 2019)
"This book examines how digital technologies enable collaboration as a way for individuals, teams and businesses to connect, create value, and harness new opportunities. Digital technologies have brought the world closer together but also created new barriers and divides. While it is now possible to connect almost instantly and seamlessly across the globe, collaboration comes at a cost; it requires new skills and hidden 'collaboration work', and the need to renegotiate the fair distribution of value in multi-stakeholder network arrangements. Presenting state-of-the-art research, case studies, and leading voices in the field, the book provides academics and professionals with insights into the diverse powers of collaboration in the digital age, spanning collaboration among professionals, organisations, and consumers. It brings together contributions from scholars interested in the collaboration of teams, cooperatives, projects, and new cooperative systems, covering a range of sectors from the sharing economy, health care, large project businesses to public sector collaboration."- Resumé vydavatel